Rhodium(I)-Catalyzed Regioselective C–H Alkenylation of 2,2′-Bipyridine Derivatives with Alkynes - Yu, Jia; Wen, Si; Tian, Qingyu; Chen, Yanhui; Cheng, Guolin (Synthesis, 2022)
In this work, a Rh(I)-catalyzed C3-alkenylation of 2,2′-bipyridine-6-carboxamide with terminal and internal alkynes was developed, providing an efficient access to a broad range of alkenylated 2,2′-bipyridine derivatives with exclusive regioselectivity and stereoselectivity. Deuterium labeling experiments indicate that an irreversible rollover C–H activation process is involved in this reaction.
Keywords: rhodium; C–H activation; rollover cyclometalation; alkenylation; 2,2′-bipyridine